The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000357871
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 and Acute Kidney Injury following Cardiac Surgery

Abstract: Background: Intraoperative hemolysis and inflammation are associated with acute kidney injury (AKI) following cardiac surgery. Plasma-free hemoglobin induces heme oxygenase-1 (HO-1) expression. HO-1 degrades heme but increases in experimental models of AKI. This study tested the hypothesis that plasma HO-1 concentrations are associated with intraoperative hemolysis and are increased in patients that develop AKI following cardiac surgery. Methods: We measured plasma HO-1, free hemoglobin, and inflammatory marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 64 publications
2
30
1
Order By: Relevance
“…The critical role of HO-1 has also been reported in several organ injuries (Wang and Dore 2007; Billings et al 2014). Given HO-1 also has been identified as a response biomarker for arsenic exposure in various types of cells, we were very interested: i) what is the role of HO-1 in As -induced nephrotoxicity (Gong et al 2014) at clinically relevant doses?…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The critical role of HO-1 has also been reported in several organ injuries (Wang and Dore 2007; Billings et al 2014). Given HO-1 also has been identified as a response biomarker for arsenic exposure in various types of cells, we were very interested: i) what is the role of HO-1 in As -induced nephrotoxicity (Gong et al 2014) at clinically relevant doses?…”
Section: Introductionmentioning
confidence: 81%
“…All these data mentioned above strongly demonstrated that HO-1 played a protective role in As -induced nephrotoxicity, and blocking HO-1 augmented As -induced cell death, ROS production and mitochondrial injury. In the other studies, HO-1 also has been shown to protect kidney against several acute kidney injury (AKI) (Billings et al 2014; Miyagi et al 2014; Goodman et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…145 Another study found increased levels of plasma HO-1 in patients who developed AKI following cardiopulmonary bypass; this is associated with duration of the bypass, hemolysis, and inflammation. 146 Given the overwhelming reliance on serum creatinine, urine output, and degree of proteinuria to monitor kidney function, the aforementioned findings of plasma and urinary HO-1 are timely and add to our armamentarium of biomarkers of AKI. However, it must also be noted that utilization of HO-1 as a novel biomarker of AKI requires additional investigation.…”
Section: Recent Advancesmentioning
confidence: 99%
“…Billings et al [59] examined the hypothesis that intravascular hemolysis induced during cardiac surgery releases plasma-free hemoglobin that in turn induces heme oxygenase-1. In patients who developed AKI after cardiac surgery, peak-free hemoglobin levels correlated with peak heme oxygenase-1, and heme oxygenase-1 levels increased with duration of CPB and interleukin activation.…”
Section: Renal Biomarkersmentioning
confidence: 99%